Exploring the Satisfaction–Revenue Nexus: A Mixed-Methods Analysis of RevPAR Performance in Southeast Asian Three-Star Hotels - Fathimah Azzahro; Bayu Irwansyah; Galih Gumilar; Devita Niken Hapsari; Dyah Palupiningtyas (An International Journal Tourism and Community Review, 2026)
This research aims to explore the satisfaction–revenue nexus by examining the effect of tourist satisfaction on Revenue Per Available Room (RevPAR) performance in three-star hotels across Southeast Asia. Grounded in Expectation–Confirmation Theory and the Service-Profit Chain framework, the study conceptualizes tourist satisfaction as a strategic intangible asset that contributes to financial performance through both direct and indirect mechanisms. A mixed-methods sequential explanatory design was employed. Quantitative panel data were collected from 312 three-star hotels in Indonesia, Malaysia, Thailand, Vietnam, and the Philippines over the period 2019–2024 and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and panel regression techniques. The results indicate that tourist satisfaction has a positive and statistically significant direct effect on RevPAR. Furthermore, occupancy rate partially mediates this relationship, suggesting that satisfaction enhances revenue performance primarily through demand stabilization and increased room utilization. Qualitative findings from managerial interviews further confirm that guest satisfaction strengthens online reputation, repeat visitation, and revenue consistency. This study contributes empirical evidence to the literature on satisfaction-driven financial performance in mid-scale hospitality markets and offers strategic implications for revenue optimization in competitive Asian contexts.